Skeletal and cranio-facial signs in Gorlin syndrome from ancient Egypt to the modern age: sphenoid asymmetry in a patient with a novel PTCH1 mutation. (June 2014) - Ponti, Giovanni; Ruini, Cristel; Pastorino, Lorenza; Loschi, Pietro; Pecchi, Annarita; Malagoli, Marcella; Mandel, Victor Desmond; Boano, Rosa; Conti, Andrea; Pellacani, Giovanni; Tomasi, Aldo
ABSTRACT: : Gorlin syndrome is an autosomal dominant disorder linked to PTCH1 mutation, identified by a collection of clinical and radiologic signs. We describe the case of a family in which father and son fulfilled clear cut diagnostic criteria for Gorlin syndrome including multiple basal cell carcinomas, keratocystic odontogenic tumors, atypical skeletal anomalies and a novel PTCH1 germline mutation (c.1041delAA). Craniofacial and other skeletal anomalies displayed at 3D and helical CT scan were: macrocephaly, positional plagiocephaly, skull base and sphenoid asymmetry, bifidity of multiple ribs and giant multilocular odontogenic jaw cysts. Extensive multilamellar calcifications were found in falx cerebri, tentorium, falx cerebelli and in the atlanto–occipital ligament. The inclusion of bifid ribs as a novel major criteri may be useful for the recognition and characterization of misdiagnosed cases.